Medication Adherence among Acute Coronary Syndrome Outpatients at Sardjito Hospital in 2019 - M Fiqri Zulpadly; Dian Eka Ermawati; Heru Sasongko (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2024)
Worldwide, heart disease accounts for the majority of deaths. One of the indications of coronary illness is Acute Coronary Syndrom (ACS) STEMI. With a prevalence rate of 7.2%, Indonesia still has the highest ACS incidence, and it continues to rise annually. Several factors are involved in reducing the mortality rate of ACS, namely by controlling several risk factors that can reduce the incidence and improve treatment. This study aims to determine the level of adherence to drug use in patients who are registered with new STEMI and outpatients at Sardjito Hospital Yogyakarta. The research method used in this study was non-experimental analytic observational with a retrospective cohort design. Measurement using the Medication Possession Ratio (MPR) method. The study population was patients who were registered for the first ACS diagnosis since January 2017 and followed the course of their treatment until the patient stopped using the drug or the end of observation (31 December 2018). The number of samples obtained according to the inclusion criteria was 495 patients. Adherence to the use of antithrombotic drugs was greater in female patients (82.4%), age < 60 years (88.4%), and patients using combination antithrombotic therapy regimens (81.4%). Statistical significance was shown in the category of gender (Log Rank = 0.046) and treatment regimen (Log Rank = 0.005). However, the age category did not show statistical significance (Log Rank = 0.289). The conclusion of this study is that adherence to the use of antithrombotic drugs in STEMI patients is influenced by gender and therapeutic regimen.